Early Postweaning Treatment with Dimethyl Fumarate Prevents Prenatal Dexamethasone- and Postnatal High-Fat Diet-Induced Programmed Hypertension in Male Rat Offspring. (15th February 2018) - Lin, Yu-Ju; Lin, I-Chun; Yu, Hong-Ren; Sheen, Jiunn-Ming; Huang, Li-Tung; Tain, You-Lin
Abstract : Prenatal dexamethasone (DEX) exposure, postnatal high-fat (HF) intake, and oxidative stress are closely related to the development of hypertension. Nuclear factor erythroid-derived 2-related factor 2 (Nrf2) regulates oxidative stress. Dimethyl fumarate (DMF) reportedly activates Nrf2 and protects against oxidative stress damage. We examined a 4-month-old male rat offspring from five groups (n = 8 for each group): control, DEX (0.1 mg/kg i.p. from a gestational age of 16 to 22 days), HF (D12331 diet from weaning to 4 months of age), and DEX + HF, DEX + HF + DMF (50 mg/kg/day via gastric gavage for 3 weeks after weaning). We found that postnatal HF intake aggravated prenatal DEX-induced hypertension in adult male offspring, which could be prevented by DMF treatment. The beneficial effects of DMF treatment include an increase in renal Nrf2 gene expression, reduction of oxidative stress, decrease in plasma asymmetric dimethylarginine (ADMA) and renal soluble epoxide hydrolase protein levels, increase in the l -arginine-to-ADMA ratio, and activation of genes related to nutrient sensing and autophagy (e.g., Pparb, Pparg, Ppargc1a, Ulk1, and Atg5 ). In conclusion, better understanding of the impact of the Nrf2 signaling pathway in the two-hit model will aid in protecting children exposed to antenatal corticosteroids and a postnatal HF diet from programmed hypertension.